Utilization of Coconut Dregs as Processed Food to Improve the Economy of the Lapeo Village Community: Pemanfaatan Ampas Kelapa sebagai Pangan Olahan Guna Meningkatkan Ekonomi Masyarakat Desa Lapeo - Isdaryanti, Isdaryanti; Nursyamsi SY; Sariyanto Putera, Alexander Kurniawan; Sari Rahayu Rahman; Phika Ainnadya Hasan; Muhammad Rizaldi Triaz Jaya Putra Nurdin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
The increase in coconut production in Lapeo Village has resulted in a rise in coconut husk waste. Regrettably, the local community tends to dispose of this waste rather than processing it. However, coconut husks, rich in nutritional content, especially fiber and protein, have the potential to be processed into various products with health benefits. Therefore, this community engagement initiative aims to provide knowledge about the nutritional content of coconut husks, followed by training sessions to process coconut husks into flour and create food products, namely semprit and banana sponge cake. Based on data analysis, this initiative has successfully increased community awareness regarding the nutritional content of coconut husks, proficiency in processing techniques, and enthusiasm for creating processed products. Furthermore, overall, this engagement contributes to opening new opportunities in utilizing coconut husk waste as a valuable high-economic-value raw material, with the hope of addressing local economic challenges and supporting environmental sustainability.